2018
DOI: 10.4103/0366-6999.233958
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Residual SYNTAX Score and Its Derived Indexes on Clinical Outcomes after Percutaneous Coronary Intervention

Abstract: Background:Residual SYNTAX score (rSS) and its derived indexes including SYNTAX revascularization index (SRI) and clinical rSS had been developed to quantify and describe the extent of incomplete revascularization. This study was conducted to explore the utility of the three scores among real-world patients after percutaneous coronary intervention (PCI).Methods:From January 2013 to December 2013, patients underwent PCI treatment at Fuwai Hospital were included. The primary endpoints were all-cause death and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Therefore, it is difficult for cardiologists to treat individuals with highly complex CAD and CRI. Furthermore, the current study demonstrated that patients with older age, increased clinical cardiac-kidney comorbidities and more anatomically complex disease, as quantified by CRSS, tended to have IR, corroborating previous reports (3,9). The RSS, which was first developed by Stone in a large cohort of acute coronary syndrome (ACS) cases, is considered an important tool for quantifying and risk-stratifying the degree and complexity of residual stenosis following PCI, with a strong independent predictive value for clinical outcomes (1).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, it is difficult for cardiologists to treat individuals with highly complex CAD and CRI. Furthermore, the current study demonstrated that patients with older age, increased clinical cardiac-kidney comorbidities and more anatomically complex disease, as quantified by CRSS, tended to have IR, corroborating previous reports (3,9). The RSS, which was first developed by Stone in a large cohort of acute coronary syndrome (ACS) cases, is considered an important tool for quantifying and risk-stratifying the degree and complexity of residual stenosis following PCI, with a strong independent predictive value for clinical outcomes (1).…”
Section: Discussionsupporting
confidence: 91%
“…Park and colleagues firstly described CRSS in patients included in a large, multicenter and all-comer PCI registry, and demonstrated that it has better predictive value for 1-year ACD and target lesion failure after PCI compared with RSS (3). Recently, Song and co-workers assessed the prognostic value of CRSS in a large-sample study examining real-world patients, and the results showed that CRSS has improved predictability of 2-year mortality than the anatomic RSS and SYNTAX revascularization index (9). However, few reports have investigated the predictive value of CRSS in CRI cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 9 10 11 ] The residual SYNTAX score, its derivative, reflecting the burden of residual coronary lesions after revascularization, was also a useful tool to quantify the incomplete revascularization and risk-stratify for CAD patients. [ 5 , 12 ] However, the major fallacy of the SYNTAX score is not accounting for the variability in the coronary anatomy, where the weighting assignment to each segment is nomenclature-based. [ 13 ] We have recently developed a new Coronary Artery Tree description and Lesion EvaluaTion (CatLet) angiographic scoring system.…”
Section: Introductionmentioning
confidence: 99%
“…To address these limitations, researchers conducted a 2-year follow-up study in 512 STEMI patients, proposed the Logistic Clinical SYNTAX score (LCSS) concept, and concluded that the LCSS has significant discrimination and acceptable calibration in predicting all-cause mortality [21] . Furthermore, it has been demonstrated through continuous improvement of SYNTAX-derived scores and subsequent studies that the clinical SYNTAX score has better predictive performance than the residual SYNTAX score for all-cause mortality 2 years after revascularization for complex CAD, whereas its predictive power for revascularization is the opposite [22] . Compared to the clinical SYNTAX score, the SYNTAX score Ⅱ demonstrated more accurate predictive performance in predicting all-cause mortality after complex CAD revascularization [18] .…”
Section: Introductionmentioning
confidence: 99%